THE IMPACT OF PEKANBARU COFFEE SHOP STRATEGY ON PURCHASE DECISIONS - Ermansyah; Rimet; Mulia Sosiady (Jotika Journal In Management and Entrepreneurship, 2024)
Purchase Decision is the final decision of the consumer to buy or not a good or service by comparing many considerations. When making a purchase decision, there are often several choices between two or more alternatives. The purpose of this study is to analyze the impact of Electronic Word Of Mouth, Sevicescape, Price Percepcion on Purchase Decision on Coffee Shop in Pekanbaru. The population in this study is 100 people using purposive sampling method. Based on the results of this study, it shows that Electronic Word Of Mouth, Sevicescape, Price Percepcion have an influence on Purchase Decision both partially and simultaneously. The results of the Determination Coefficient (R2) showed that the magnitude of the influence of both free variables together on the bound variable was 54.7%, while the remaining 45.3% were other variables not studied in this study.